The Importance of Students' Attitudes Towards English for Instruction in Heterogeneous Classes - Klemen Blatnik, Nina; Bratož, Silva (Revija za elementarno izobraževanje, 2022)
The article investigates the impact factors which influence pupils' attitudes towards learning English as a foreign language, since these represent an important source of information for planning lessons in heterogeneous or mixed ability classes. The empirical part presents the results of a study among third graders (n=90), aimed at identifying the impact of the following factors on their attitudes: the age at which they started learning English, their gender, the exposure to English in their home environment and the valuable others (teachers, parents, and peers). The results suggest that in this age group, parents and teachers have a more salient influence on the learners' attitudes towards English than their peers.
Keywords: heterogeneous classes, foreign language attitudes, foreign language motivation, valuable others, English as a foreign language